Permasalahan Dalam Pembelajaran Kurangnya Minat Belajar - Aulia Rahma Pramita; Aprilistia Nugraheni; Rindi Sagita; Della Aprilyana (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The decline in interest in learning among students has become an issue of concern in the world of education, which has the potential to hinder their academic development and skills. This research was conducted to identify the factors that cause low interest in learning and look for potential solutions to overcome them. Using the literature study method, this research examines relevant literature from scientific journals, books and other articles to gain an in-depth understanding of the topic. The results of the study show that several factors, such as a monotonous learning approach, lack of environmental support, and the influence of technology, have a negative impact on students' interest in learning. It is hoped that this article can contribute to identifying more effective strategies for increasing interest in learning and can become a reference for researchers and educational practitioners.